Examples of ultrasonic detection of partial discharges in case of 110 kV instrument transformers - Milić Momčilo; Jovanović Đorđe; Radin Vesna; Dimitrijević Marko (Zbornik Radova: Elektrotehnički Institut "Nikola Tesla")
Instrument transformers are a critical component of power plants, widely distributed due to their essential role in measuring and protecting the entire power system. Given their continuous exposure to environmental and electrical stresses, and the potential for explosive failures that can jeopardize power facility operations and disrupt power supply, regular electrical testing is crucial to assess their condition and operational reliability. One non-invasive testing method for instrument transformers is acoustic (ultrasound) analysis. This technique involves placing an acoustic piezo-sensor on the grounded wall of the transformer tank, at a safe distance from high-voltage components. Short-term data acquisition and subsequent analysis are then performed. This method is particularly advantageous for power plants as it requires minimal intervention and does not necessitate disconnecting the transformer from operation. Acoustic detection of partial discharges is often complemented by gas chromatographic analysis of insulating oil. This combined approach provides robust confirmation of partial discharge activity within the transformer's insulation system. This paper will present case studies of ultrasonic detection of partial discharges on 110 kV instrument transformers, where chemical analysis of oil samples corroborated the presence of these detrimental discharges.